If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(9a + 4b) + -8(a + 8b) = 0 (9a * 3 + 4b * 3) + -8(a + 8b) = 0 (27a + 12b) + -8(a + 8b) = 0 27a + 12b + (a * -8 + 8b * -8) = 0 27a + 12b + (-8a + -64b) = 0 Reorder the terms: 27a + -8a + 12b + -64b = 0 Combine like terms: 27a + -8a = 19a 19a + 12b + -64b = 0 Combine like terms: 12b + -64b = -52b 19a + -52b = 0 Solving 19a + -52b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '52b' to each side of the equation. 19a + -52b + 52b = 0 + 52b Combine like terms: -52b + 52b = 0 19a + 0 = 0 + 52b 19a = 0 + 52b Remove the zero: 19a = 52b Divide each side by '19'. a = 2.736842105b Simplifying a = 2.736842105b
| -5(4q+2)=-3q+10 | | r=-20+10a | | -3*-8-9= | | 3=4(x+3)-5 | | -79+12x=38+3x | | 9y-9=9y-y | | 44-3x=15x+16 | | 2(5-4)= | | (2-5)= | | 7*-2+3= | | 0.08x+0.07(15000-x)=1110 | | 2k+h=1 | | -3x-4(-0.5+-0.75)=2 | | 5*3+4= | | -32+9x=8+5x | | X-8=2x+9 | | -2x^3(3x^2-6x-1)= | | -7z-49=2-6z | | -3(-2.6-1)+5=2(-2.6+1)-3(-13-1)+13 | | -29+x=-7x+51 | | h+2k=14k | | 3.4x-4.6=2.2 | | -46+2x=30+6x | | 12k=1-2k | | 6m-5=7m+5-m | | 19-h-h=-18 | | 7-(9x+3)=-9x-4 | | x(7+66)= | | y=2-5+-2.5 | | 7-x+4=27 | | x^8-24x^4+128=0 | | 4x*2+9x+22=0 |